Subsistence economy in the South Caucasus during the Early Chalcolithic period: bioarchaeological analysis of Bavra Ablari rock-shelter (Samtskhe-Javakheti region, Georgia) - Decaix, Alexia; Martin, Lucie; Messager, Erwan; Chahoud, Jwana; Varoutsikos, Bastien; Mgeladze, Ana; Gabunia, Manana; Agapishvili, Tamar; Chataigner, Christine (Frontiers in Environmental Archaeology, 2024)
This paper examines the subsistence economy in the South Caucasus during the Early Chalcolithic (c. 4700-4300 BC) through bioarchaeological analyses of the Bavra Ablari rock shelter site. This region, rich in biodiversity and characterised by a variety of climates and landscapes, has a history of agropastoral occupation dating back to the beginning of the 6 th millennium BC. Up to now, archaeological studies have mainly focused on the valleys and lowlands, leaving the mountainous areas less explored. Recent excavations at Bavra Ablari, located at an altitude of 1,650 m, have enabled new bioarchaeological analyses to be carried out, providing data on the faunal and botanical assemblages of this period. These analyses reveal a mixed agro-pastoral exploitation, with a predominance of caprine (sheep and goats) rearing and cultivation of cereals, such as barley and einkorn. Faunal remains and evidence of hunting and fishing reveal extensive use of several biotopes. The study highlights the importance of pastoralism, attested to as far back as the Neolithic period, with herds moving seasonally to higher pastures in summer. Early Chalcolithic occupations, such as those at Bavra Ablari, show the persistence of pastoral activities in these mountainous regions despite severe winter conditions and suggest seasonal occupation of the site.